Accelerated Aging Process of Bio-Oil Model Compounds: A Mechanism Study - Wang, Rui; Ben, Haoxi (Frontiers in Energy Research, 2020)
Bio-oil, obtained from the pyrolysis of biomass, is identified as a potential material to produce transportation fuels and value-added chemicals. However, physical and chemical properties of bio-oil change versus time, known as “aging”, and the instability of bio-oil brings a critical hurdle to the commercial application of bio-oil. Therefore, expanding and deepening the understanding of aging mechanism of bio-oil is the key for later efficient application of bio-oil. In addition, the extreme complexity of pyrolysis bio-oil composition brings great difficulties in studying the aging mechanism. Thus, this study tries to better understand the aging mechanism by evaluating the aging performance for 39 model compound aging tests performed at 80℃ for 72 hours. Four kinds of reactions (self-condensation, esterification, aldol condensation, and phenol and aldehyde reaction) were investigated to understand the contribution of various compounds and reactions during aging process. It has been found that acid played an important role in aging process, as it acted as the reactant in esterification reaction and acted as the catalysis for aldol condensation and phenol and aldehyde reaction. Acids and alcohols reacted via esterification reaction, resulting in the decline of aliphatic C-O bonds. Due to the absence of acid, aromatic compounds were relatively stable in these tests. In comparison, aldehydes and HMF were active since self-condensation reactions for these chemicals were observed in absence of acid. Moreover, with the aid of acid, HMF showed high tendency towards polymerization, result in the increasing water content and molecule weight during accelerated aging process.